The Structural and Optical Properties of Perovskite Thin Films (European Journal of Formal Sciences and Engineering, 2022)
Perovskite materials have many interesting properties such as modulation of the optical band gap and the properties of quantum wells. In addition, they have a stable structure. For these reasons, perovskites have attractive properties for optoelectronic devices. Additionally, the structural and optical properties can be changed by means of different halide atoms doped into materials. In this study, the effect of iodine on the structural, and optical properties of perovskite thin films was investigated. KCaCl2 I and KCaCl3 perovskite were prepared by chemical bath deposition on a glass substrate. The crystal structures of the films were determined by X-ray diffraction. X-Ray Diffraction (XRD) analysis revealed that the films had a crystalline structure. In addition, KCaCl2 I perovskite thin film has better crystalline than KCaCl3 perovskite thin films. Linear optical parameters were determined using transmittance and absorbance measurements. And then, the optical band gap values, extinction coefficient, refractive index, and dielectric constants were determined as linear optical properties. It was understood that these properties were affected by iodine.